Contextual picture storybooks to improve reading interest and beginning reading skills among first-grade primary school students (Diniyah: Jurnal Pendidikan Dasar, 2026)
Early-grade reading instruction should cultivate both children’s interest in reading and their ability to decode and understand simple texts. This study aimed to analyze how contextual picture storybooks improved first-grade students’ reading interest and beginning reading skills through reflective classroom action. The study involved 26 first-grade students at an Indonesian primary school and was conducted in two action cycles. Data were collected through reading interest observation sheets, beginning reading performance assessments, field notes, and classroom documentation. The findings showed consistent improvement across cycles. Students’ reading interest increased from 57.7% in the pre-action stage to 73.1% in Cycle I and 88.5% in Cycle II. Beginning reading mastery also improved from 50.0% to 69.2% and then to 84.6%, while the average reading score increased from 59.6 to 81.9. These improvements were supported by picture walk, guided reading, expressive reading, peer support, and locally contextualized stories. The study implies that picture storybooks can serve as effective pedagogical tools for strengthening early literacy engagement and reading performance. Keywords: beginning reading; classroom action research; early literacy; picture storybooks; primary school; reading interest